Humanizing corporate governance among Malaysian corporations: the role of virtue ethics, ethical leadership and culture - Yap, Kuan Yi (2021)
The notion of profit-maximisation and greed have motivated corporations to commit fraud and corruption, often triggered by failed leadership and distorted culture. Recurring incidences of corporate scandals have led to questions of corporate accountability creating a need for organisations to move beyond compliance. The objective of this study is to investigate the role of virtues, culture and leadership together in strengthening governance and accountability of every corporate participant. Using questionnaires collected from working adults in Malaysia, we find that ethical culture and ethical leadership mediates the relationship between virtue ethics and governance indicating that virtue ethics enhances both ethical culture and ethical leadership leading to good governance practices. These findings provide timely and meaningful implications to companies which help them reducing incidences of fraud and mismanagement, promoting organisation commitment and more importantly, stakeholder protection. The findings also contribute towards an understanding the importance and application of virtues ethics in corporate setup.